(x-35) - 120 = 0
=> x - 35 = 120
=> x = 155
124 + (118 - x) = 217
=> 118 - x = 217 - 124 = 93
=> x = 118 - 93 = 25
156 - (x+61) = 82
=> x + 61 = 156 - 82 = 74
=> x = 74 - 61 = 13
Đúng 0
Bình luận (0)
a, \(\left(x-35\right)-120=0\)
\(\Rightarrow x-35=120\)
\(\Rightarrow x=120+35\)
\(\Rightarrow x=155\)
b, \(124+\left(118-x\right)=217\)
\(\Rightarrow118-x=217-124\)
\(\Rightarrow118-x=93\)
\(\Rightarrow x=118-93\)
\(\Rightarrow x=25\)
c, \(156-\left(x+61\right)=82\)
\(\Rightarrow x+61=156-82\)
\(\Rightarrow x+61=74\)
\(\Rightarrow x=74-61\)
\(\Rightarrow x=13\)
Đúng 0
Bình luận (0)
a) ( x - 35 ) - 120 = 0
<=> x - 35 = 120
<=> x = 155
b) 124 + ( 118 - x ) = 217
<=> 118 - x = 93
<=> x = 25
c) 156 - ( x + 61 ) = 82
<=> x + 61 = 74
<=> x = 13
Đúng 0
Bình luận (0)